Numerical analysis of non-Newtonian nanofluids under double-diffusive regimes - Sher Akbar, Noreen; Mallawi, Fouad Othman (Frontiers in Materials, 2023)
In the present study, the velocity slip non-Newtonian fluid flow above a continuously stretching surface with double-diffusive nanofluid has been examined at stipulated superficial temperature counting the salt concentration. The leading partial differential equations along with the boundary conditions are originally troupe into a dimensionless form and then the comparation variables are invoked to diminish the partial differential equations into the ordinary differential equation, then the condensed ordinary differential equations are solved numerically via the shooting scheme. The values of the dimensionless velocity, temperature, salt concentration dispersal, the local Nusselt number, and Sherwood number are obtained numerically and presented in tabulated form through graphs. A extensive parametric study is conduced to probe the elaborate parameter’s effect for both assisting and opposing flow.